2015
DOI: 10.1590/1413-81232014201.21732013
|View full text |Cite
|
Sign up to set email alerts
|

Men's health in question: seeking assistance in primary health care

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0
32

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 8 publications
1
13
0
32
Order By: Relevance
“…In the sample studied men and women were homogeneous with respect to age, but the hospitalization and mortality rates in men were higher than in women. This result may be related to the behaviors and life styles of men, who exhibit lower adherence to preventive care and increased exposure to harmful health habits (26)(27)(28)(29)(30) . Limitations of this study were performing in a single center and the use of protocol developed locally, which limited the comparison with other studies and that can make it difficult to generalize the results to other populations and regions.…”
Section: Discussionmentioning
confidence: 99%
“…In the sample studied men and women were homogeneous with respect to age, but the hospitalization and mortality rates in men were higher than in women. This result may be related to the behaviors and life styles of men, who exhibit lower adherence to preventive care and increased exposure to harmful health habits (26)(27)(28)(29)(30) . Limitations of this study were performing in a single center and the use of protocol developed locally, which limited the comparison with other studies and that can make it difficult to generalize the results to other populations and regions.…”
Section: Discussionmentioning
confidence: 99%
“…Em ambas as fases deste estudo, houve maior porcentagem de mulheres. É sabido que a busca pelos serviços de saúde é habitualmente feminina, por outro lado a não procura pelos atendimentos em saúde por parte dos idosos do sexo masculino, pode estar relacionada com o papel social construído para o homem, que engloba atributos de competitividade e de robustez 21 . Outro fator relevante diz respeito à "feminização" da população, sendo um processo comumente observado na população brasileira 22 .…”
Section: Discussionunclassified
“…15 The men's culture is pointed out as another factor adding to non-adherence of men to health care measures and prevention services, which may be a reflection of the social role constructed for men, in which masculinity is tied to values or attributes such as strength, aggressiveness, competitiveness and sexuality, contributing to determine, for example, the morbidity and mortality profile of these subjects. 12,18 A study carried out in Spain found out that the life expectancy of men is 78.5 years, six years less than that of women. It is known that the mortality rate from chronic diseases in people under 75 years of age is highly unfavorable to men and includes more mortality from diseases that occur mainly as a result of poor health habits.…”
mentioning
confidence: 99%